The Influence of Dividend Policy, Capital Structure, and Investment Opportunity Set on the Firm Value in the Technology Sector Industry : Study on Technology Industry Sector Companies Listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022 - Annisya Uzzaqia H; Mahatma Kufepaksi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this study is to analyze the influence of dividend policy, capital structure, and investment opportunity set on firm value in the technology sector industry (A Study of Technology Sector Companies Listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022). This study uses a quantitative approach with secondary data. The population of this study consists of companies operating in the technology industry that have gone public and are listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The data collection method used is secondary data. The secondary data collection method was obtained from data available at the Indonesia Stock Exchange (IDX). The data processing techniques used in this study involved secondary data analysis conducted by the researcher with the assistance of E-Views 9 software. The results of this study indicate that dividend policy has a positive and significant effect on firm value, suggesting that investors in the technology sector still view dividends as a signal of financial stability. Capital structure has a positive and significant effect on firm value, indicating that optimal debt usage can enhance competitiveness and growth in the technology sector. Investment opportunities also have a positive and significant impact on firm value, as companies with high investment prospects are more attractive to investors and experience increased stock prices. Dividend policy, capital structure, and investment opportunities simultaneously have a significant impact on firm value, with firm size and profit growth as control variables that also strengthen this relationship.